Service delivery challenges in HIV care during the first year of the COVID‐19 pandemic: results from a site assessment survey across the global IeDEA consortium. Issue 12 (11th December 2022) - Brazier, Ellen; Ajeh, Rogers; Maruri, Fernanda; Musick, Beverly; Freeman, Aimee; Wester, C. William; Lee, Man‐Po; Shamu, Tinei; Crabtree Ramírez, Brenda; d'Almeida, Marcelline; Wools‐Kaloustian, Kara; Kumarasamy, N.; et al.
Abstract: Introduction: Interruptions in treatment pose risks for people with HIV (PWH) and threaten progress in ending the HIV epidemic; however, the COVID‐19 pandemic's impact on HIV service delivery across diverse settings is not broadly documented. Methods: From September 2020 to March 2021, the International epidemiology Databases to Evaluate AIDS (IeDEA) research consortium surveyed 238 HIV care sites across seven geographic regions to document constraints in HIV service delivery during the first year of the pandemic and strategies for ensuring care continuity for PWH. Descriptive statistics were stratified by national HIV prevalence (<1%, 1–4.9% and ≥5%) and country income levels. Results: Questions about pandemic‐related consequences for HIV care were completed by 225 (95%) sites in 42 countries with low ( n = 82), medium ( n = 86) and high ( n = 57) HIV prevalence, including low‐ ( n = 57), lower‐middle ( n = 79), upper‐middle ( n = 39) and high‐ ( n = 50) income countries. Most sites reported being subject to pandemic‐related restrictions on travel, service provision or other operations (75%), and experiencing negative impacts (76%) on clinic operations, including decreased hours/days, reduced provider availability, clinic reconfiguration for COVID‐19 services, record‐keeping interruptions and suspension of partner support. Almost all sites in low‐prevalence and high‐income countries reported increased use of telemedicine (85% and 100%, respectively), compared with less than half of sites in high‐prevalence and lower‐income settings. Few sites in high‐prevalence settings (2%) reported suspending antiretroviral therapy (ART) clinic services, and many reported adopting mitigation strategies to support adherence, including multi‐month dispensing of ART (95%) and designating community ART pick‐up points (44%). While few sites (5%) reported stockouts of first‐line ART regimens, 10–11% reported stockouts of second‐ and third‐line regimens, respectively, primarily in high‐prevalence and lower‐income settings. Interruptions in HIV viral load (VL) testing included suspension of testing (22%), longer turnaround times (41%) and supply/reagent stockouts (22%), but did not differ across settings. Conclusions: While many sites in high HIV prevalence settings and lower‐income countries reported introducing or expanding measures to support treatment adherence and continuity of care, the COVID‐19 pandemic resulted in disruptions to VL testing and ART supply chains that may negatively affect the quality of HIV care in these settings.